Teacher Assistance in Implementing Process-Based Differentiated Learning at SDN 105 Kendari - Nujmiati; Putri Dwi Humaerah; Suharsono Bantun (Teras Kampus as a member of PT Palem Edukasi Nusantara, 2026)
Differentiated instruction is a learning approach that aims to accommodate the diverse learning needs of students. However, its implementation in elementary schools remains challenging, particularly due to teachers’ limited understanding and experience in designing and applying adaptive learning strategies. This community service program aimed to provide teacher mentoring in implementing process-based differentiated instruction in reading lessons at SDN 105 Kendari. The program employed a participatory mentoring approach that positioned teachers as active partners through four main stages: identification of students’ learning needs through initial assessment, planning of differentiated instruction, classroom implementation, and reflection and evaluation. Data were collected through classroom observations, students’ assessment results, teacher reflections, student feedback, and activity documentation, and were analyzed using a descriptive qualitative approach. The results indicated that teacher mentoring enhanced teachers’ pedagogical competence in designing and implementing process differentiation through varied reading activities, including independent reading, group reading, and oral reading in front of the class. The implementation of process-based differentiated instruction positively impacted students’ engagement and self-confidence in reading activities. The novelty of this program lies in the reflective and sustainable teacher mentoring model that supports the implementation of the Merdeka Curriculum in elementary schools.